2015
DOI: 10.1155/2015/180972
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc and Optic Cup Segmentation Methodologies for Glaucoma Image Detection: A Survey

Abstract: Glaucoma is the second leading cause of loss of vision in the world. Examining the head of optic nerve (cup-to-disc ratio) is very important for diagnosing glaucoma and for patient monitoring after diagnosis. Images of optic disc and optic cup are acquired by fundus camera as well as Optical Coherence Tomography. The optic disc and optic cup segmentation techniques are used to isolate the relevant parts of the retinal image and to calculate the cup-to-disc ratio. The main objective of this paper is to review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 58 publications
(78 reference statements)
0
93
0
7
Order By: Relevance
“…Interestingly, since cup-to-disc ratio is used to measure the progression of glaucoma [3], a number of investigations have explored the potential connection between glaucoma and AD. Two of these studies examined AD patients and found a relationship with one reporting that 25.9 % of the sample was positive for glaucoma, a condition that is only prevalent in about 5 % of the general population [16, 171].…”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, since cup-to-disc ratio is used to measure the progression of glaucoma [3], a number of investigations have explored the potential connection between glaucoma and AD. Two of these studies examined AD patients and found a relationship with one reporting that 25.9 % of the sample was positive for glaucoma, a condition that is only prevalent in about 5 % of the general population [16, 171].…”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 99%
“…However, apparent differences between glaucoma and the ocular manifestations of AD challenge such a notion. While glaucoma shows optic disc cupping accompanied by a specific pattern of loss in the optic nerve and GCL [3, 41], the ocular findings in AD have overwhelmingly indicated damage to the NFL and GCL along with hallmark molecular signs in peripheral retinal regions [2022, 81, 107, 113, 163]. Since evidence linking the two diseases remains controversial, further research would be warranted before claims of common etiology could be made about these diseases.…”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 99%
“…Segundo Haleem et al (2013) os métodos podem ser divididos em duas categorias: métodos baseados em modelo e métodos não baseados em modelo. Já Almazroa et al (2015), sugere uma classi cação baseada na principal técnica de segmentação utilizada. Assim, os autores classi caram os métodos em oito grupos.…”
Section: Métodos De Segmentaçãounclassified
“…Avaliamos que a classi cação baseada na principal técnica utilizada re ete melhor os trabalhos da última década. Contudo, diferente de Almazroa et al (2015), classi camos os trabalhos em menos grupos por intender que há interseções entre os grupos propostos por Almazroa et al (2015). Assim os artigos foram classi cados em cinco grupos: algoritmos de Agrupamento, algoritmos de superpixel, Contorno Ativo, Morfologia Matemática e redes neurais convolucionais.…”
Section: Métodos De Segmentaçãounclassified
“…A number of methods have been presented in the literature for automatic segmentation of disc and cup [4]. Existing Optic disc segmentation techniques based on active contours [3,5] and morphological feature [5] are capable of producing reliable OD boundary.…”
Section: Introductionmentioning
confidence: 99%